A participação da sociedade no planejamento educacional: o caso do Plano Municipal de Educação em um município do sertão de Alagoas - Silva, Luciene Amaral da (2019)
This thesis sought to analyze how the participation of civil society in educational planning is configured from the performance in the Municipal Education Plan 2015-2025 in the municipality of Santana do Ipanema, in the state of Alagoas, through the Municipal Education Forum of Education, body responsible for the preparation, monitoring and evaluation of the municipal education decenal plan. The research was developed from the approach of the case study that allows the analysis of the social phenomenon from the reality that aims to observe the particularities of the case in the proposal to avoid analytical generalizations (YIN, 2001). The instrument used in data collection was the semi-structured interview applied to the members of the Municipal Education Forum. The collected data were analyzed from the framework of Bardin Content Analysis (1977) based on the categories of participation and civil society. The epistemological theoretical approach adopted was based on gramsci's studies (1981;1982;1984; 1999;2007) based on the conception of civil society as a space of conflict and participation as social intervention. The initial hypothesis came from the analysis of the existing fragility in the current participation model that is not able to become a de facto social participation, whose counselors and other members of the deliberative bodies act in a fragile way. The results showed that the way participation is configured promotes the legitimation of the project of economically favored classes, hindering the performance of civil society in the planning of public educational policies, but that the forums, councils as other deliberative bodies still remain learning spaces for the exercise of democracy.